The Formation of Defect‐Pairs for Highly Efficient Visible‐Light Catalysts. Issue 11 (23rd January 2017) - Sun, Qingbo; Cortie, David; Zhang, Shaoyang; Frankcombe, Terry J.; She, Guangwei; Gao, Jie; Sheppard, Leigh R.; Hu, Wanbiao; Chen, Hua; Zhuo, Shangjun; Chen, Dehong; Withers, Ray L.; et al.
Abstract : Highly efficient visible‐light catalysts are achieved through forming defect‐pairs in TiO2 nanocrystals. This study therefore proposes that fine‐tuning the chemical scheme consisting of charge‐compensated defect‐pairs in balanced concentrations is a key missing step for realizing outstanding photocatalytic performance. This research benefits photocatalytic applications and also provides new insight into the significance of defect chemistry for functionalizing materials.